2020
DOI: 10.1590/1413-7054202044025119
|View full text |Cite
|
Sign up to set email alerts
|

Rootstocks for the new seedless table grape ‘BRS Vitória’ under tropical semi-arid conditions of São Francisco Valley

Abstract: ‘BRS Vitoria’ is the most important Brazilian table grape cultivar in the domestic and foreign markets, standing out for the seedleness, pleasant flavor, high yield and mildew resistance. The aim of the present study was to determine the effect of the rootstock on the yield, production components, vigor, and physical and chemical characteristics of the ‘BRS Vitória’ grape under irrigation in the Brazilian semi-arid region. The experiment was conducted over eight consecutive production cycles in the period from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 13 publications
2
6
2
Order By: Relevance
“…The results obtained differed from those observed in this same region for 'BRS Vitória' on different rootstocks, where there was no significant effect of rootstocks on grapevine yield; the grapevines achieved 22.0 t·ha -1 only from the fifth production cycle on (Leão et al 2020b). The 'BRS Melodia' can reach mean yields of 25 t·ha -1 as of the second production cycle under tropical conditions when the grapevines remain at rest 60 to 70 days to restore reserves (Ritschel et al 2021).…”
Section: Resultscontrasting
confidence: 91%
See 3 more Smart Citations
“…The results obtained differed from those observed in this same region for 'BRS Vitória' on different rootstocks, where there was no significant effect of rootstocks on grapevine yield; the grapevines achieved 22.0 t·ha -1 only from the fifth production cycle on (Leão et al 2020b). The 'BRS Melodia' can reach mean yields of 25 t·ha -1 as of the second production cycle under tropical conditions when the grapevines remain at rest 60 to 70 days to restore reserves (Ritschel et al 2021).…”
Section: Resultscontrasting
confidence: 91%
“…The rootstocks IAC 572 and IAC 313 led to development of berries with a diameter within the values recommended for commercialization of in the four production cycles evaluated (Ritschel et al 2021). Similar to the results found in this study, other table grape cultivars, such as 'Flame Seedless' (Ibacache et al 2016), 'Thompson Seedless' (Martinez et al 2017), and 'BRS Vitória' (Leão et al 2020b), also exhibited values of berry diameter suitable for commercialization for all the rootstocks studied. Mean values followed by the same lowercase letters in the column comparing rootstocks and uppercase letters in the row comparing production cycles do not differ by Tukey's test (p < 0.05); CV: coefficient of variation.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The results obtained in this trial showed that the rootstock affected each table grape cultivar in a different way, confirming a genotype-dependent response already shown in different studies conducted on table grape (Leão et al 2020a(Leão et al , 2020b, juice (Leão et al 2022), and wine Chaves 2019, 2021)…”
Section: Resultssupporting
confidence: 86%